2020
DOI: 10.1016/j.heliyon.2020.e04516
|View full text |Cite
|
Sign up to set email alerts
|

Disconnection of the right superior parietal lobule from the precuneus is associated with memory impairment in oldest-old Alzheimer's disease patients

Abstract: There is a wide range of onset age in Alzheimer's disease (AD). Emerging evidence indicates variation of AD manifestations in oldest-old AD (OOAD); however, the pattern of cognitive dysfunctions remains unclear. We aimed to reveal cognitive performance characteristics and changes in brain functional connectivity in OOAD patients by a resting-state fMRI (rs-fMRI) study. We enrolled AD patients who had been referred to Kyushu University Hospital (KUH) or Sanno Hospital, and classified them into middle-old AD (MO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 63 publications
(73 reference statements)
3
3
0
Order By: Relevance
“…The cross-sectional study also found greater bilateral frontoparietal connectivity that predicted better visuospatial performance for the oldestold (Jiang et al, 2020), whereas the longitudinal study observed age-related increases in connectivity between the insula and supplementary motor area, with precuneus connectivity relating to changes in general cognitive performance (Li et al, 2020). Results of both studies were independent of whole brain volume and comparable to findings within younger-old and oldest-old adults with Alzheimer's disease (e.g., in the default mode network; Prawiroharjo et al, 2020), suggesting that they are not driven by cognitive dysfunction.…”
Section: Brain and Neurocognitive Aging In The Oldest-oldsupporting
confidence: 51%
“…The cross-sectional study also found greater bilateral frontoparietal connectivity that predicted better visuospatial performance for the oldestold (Jiang et al, 2020), whereas the longitudinal study observed age-related increases in connectivity between the insula and supplementary motor area, with precuneus connectivity relating to changes in general cognitive performance (Li et al, 2020). Results of both studies were independent of whole brain volume and comparable to findings within younger-old and oldest-old adults with Alzheimer's disease (e.g., in the default mode network; Prawiroharjo et al, 2020), suggesting that they are not driven by cognitive dysfunction.…”
Section: Brain and Neurocognitive Aging In The Oldest-oldsupporting
confidence: 51%
“…The cross-sectional study also found age-related increases in bilateral frontoparietal connectivity that predicted better visuospatial performance for the oldest-old (Jiang et al, 2020), whereas the longitudinal study observed age-related increases in connectivity between the insula and supplementary motor area, with precuneus connectivity relating to general cognitive performance (Li et al, 2020). Results of both studies were independent of whole brain volume loss and comparable to findings within younger-old and oldest-old adults with Alzheimer's disease (e.g., in the default mode network; Prawiroharjo et al, 2020), suggesting that they reflect normal aging processes.…”
Section: Brain and Neurocognitive Aging In The Oldest-oldsupporting
confidence: 49%
“…In particular, AD-HCR patients compared with AD-LCR showed reduced thickness in a cluster included the post-central gyrus (BA3), the precuneus (BA7) and the posterior cingulate cortex (BA31). The precuneus and the posterior cingulate cortex have been previously recognised as involved in memory functioning [48][49][50]. AD-HCR patients showed also thinner thickness in the BA44 (i.e., Broca's area), which is implicated in speech production.…”
Section: Discussionmentioning
confidence: 99%